SYNTHESIS AND QUANTUM-CHEMICAL ANALYSIS OF A COMPLEX COMPOUND OF Cu(II) ION WITH INDOLE-3-ACETIC ACID AND ACETAMIDE - Ismailova , Shahla; Ibragimov , Sapajan; Khudoyberganov , Oybek (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article presents the results of the synthesis and quantum-chemical analysis of a new mixed-ligand coordination compound based on the divalent copper (II) ion with indole-3-acetic acid (IAA) and acetamide (AA) ligands. The aim of the study is to determine the conditions for the formation of the complex compound and to investigate its composition, structure, and electronic properties using modern physicochemical methods. Elemental analysis of the synthesized complex confirmed its stoichiometric composition, while IR spectroscopy revealed the coordination modes of the ligands to the metal ion. In particular, it was established that indole-3-acetic acid participates in coordination through the carboxylate group, whereas acetamide coordinates via the carbonyl oxygen atom. In the theoretical part of the study, the geometric structure of the complex was optimized using Density Functional Theory (DFT), and its stability was evaluated. Quantum-chemical calculations were performed to determine the Mulliken charge distribution of atoms in the molecule, the energies of the HOMO and LUMO orbitals, and the energy gap (ΔE). The obtained results indicate the high stability and reactivity of the complex compound.Furthermore, these parameters are of significant importance for predicting the plant growth-stimulating properties of the complex. The results of this study can be applied in the fields of coordination chemistry, bioinorganic chemistry, and the development of new agricultural stimulants.